Pre-surgical Alveolar Molding: An Adjunct to Surgical Repair in Cleft Lip and Palate Rehabilitation - Pande, Rikta; Koirala, Bandana; Dali, Mamta; Poudel, Kabiraj (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Bilateral cleft lip and palate (CLP) with a severely protruded premaxillary segment can present as a challenge during surgical lip repairing. Pre-surgical alveolar molding, as described in this case report, is one such technique which aids in the approximation of the cleft segments thereby improving the esthetic result of the surgical repair. The present case highlights the importance of a simple molding appliance in re-positioning the protruded premaxillary segments of a neonate with bilateral CLP thereby serving as an adjunct to the surgical repair.